Murradambirra Dhangaang (make food secure): Aboriginal community and stakeholder perspectives on food insecurity in urban and regional Australia - Simone Sherriff; Deanna Kalucy; Allison Tong; Nawazish Naqvi; Janice Nixon; Sandra Eades; Tangerene Ingram; Kym Slater; Michelle Dickson; Amanda Lee; Sumithra Muthayya (BMC, 2022)
Abstract Background It is widely acknowledged that the invasion by colonial powers of the Australian continent had profound and detrimental impacts on Aboriginal Communities, including food security. Policies of successive governments since European arrival have since further exacerbated the situation, with food insecurity now affecting 20-25% of Aboriginal and Torres Strait Islander people. Food insecurity contributes to long-term impacts on health, in particular diet-sensitive chronic diseases. This study aimed to describe Aboriginal community and stakeholder perspectives on food insecurity to get a better understanding of the key contributing factors and recommendations for potential strategies to address this issue in Aboriginal communities in urban and regional Australia. Methods Semi-structured interviews were conducted with 44 participants who were purposively selected. This included Aboriginal people in two communities and both Aboriginal and non-Aboriginal stakeholders from local food relief agencies, food suppliers, schools, and government in an urban and regional location in NSW. A conceptual framework was developed from literature on food security, and sensitizing concepts of availability, affordability, accessibility and acceptability or the lack thereof of healthy food were used to elicit responses from the participants. Interview transcripts were analysed thematically. Results All participants felt strongly that food insecurity was a major problem experienced in their local Aboriginal communities. Five core areas impacting on food security were identified: trapped in financial disadvantage; gaps in the local food system; limitations of non-Aboriginal food relief services; on-going impacts of colonization; and maintaining family, cultural and community commitments and responsibilities. Participants suggested a number of actions that could help ease food insecurity and emphasized that Aboriginal values and culture must be strongly embedded in potential programs. Conclusions This study found Aboriginal families in urban and regional Australia are experiencing food insecurity on a regular basis, which is impacted by a range of socio-economic, environmental, systemic and cultural factors, as reported by the participants. Study findings highlight the need to address system level changes in the food environment and acknowledge Aboriginal history, culture and food preferences when considering the development of programs to alleviate food insecurity among Aboriginal people.